2015
DOI: 10.1093/bja/aeu559
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral regional anaesthesia and outcome: lessons learned from the last 10 years

Abstract: The majority of peripheral regional anaesthetic techniques have been shown to produce benefits for patients and hospital efficiency. Further interventional trials are required to clarify such benefits for supraclavicular block and transversus abdominis plane block and to ascertain any longer-term benefits for almost all of the blocks reviewed. Permanent complications of peripheral regional anaesthetic blocks are rare but accurate estimates of their incidence are yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 193 publications
(162 reference statements)
1
88
0
1
Order By: Relevance
“…This is confirmed by a recent metaanalysis, which found marginal postoperative analgesic efficacy of transversus abdominis plane block after abdominal laparotomy/laparoscopy and cesarean delivery [10]. Consistent with the aforementioned study by the multisociety panel [7 && ], the review [9] found that the evidence for the impact of peripheral nerve blocks on longer-term outcomes was inadequate to inform clinical decision-making.…”
Section: Alternatives To Neuraxial Analgesiasupporting
confidence: 54%
See 1 more Smart Citation
“…This is confirmed by a recent metaanalysis, which found marginal postoperative analgesic efficacy of transversus abdominis plane block after abdominal laparotomy/laparoscopy and cesarean delivery [10]. Consistent with the aforementioned study by the multisociety panel [7 && ], the review [9] found that the evidence for the impact of peripheral nerve blocks on longer-term outcomes was inadequate to inform clinical decision-making.…”
Section: Alternatives To Neuraxial Analgesiasupporting
confidence: 54%
“…The main advantages over neuraxial analgesia are the avoidance of potentially catastrophic neurologic complications associated with spinal procedures, the higher hemodynamic stability and the lesser impairment of motor function. A recent narrative review based on a systematic literature search and prospectively defined appraisal criteria came to the conclusion that the majority of peripheral regional anesthetic techniques produce benefits for patients and hospital efficiency: they reduce postoperative pain and opioid consumption and/or increase patient satisfaction; for selected surgical procedures, the use of blocks can avoid general anesthesia and is associated with increased efficiency of the surgical pathway [9]. An exception is the transversus abdominis plane block, where the evidence for efficacy was conflicting.…”
Section: Alternatives To Neuraxial Analgesiamentioning
confidence: 99%
“…Biomarkers related to active synovitis are also investigated. In this respect, it is demonstrated that plasma levels of vascular endothelial growth factor (VEGF), matrix metalloprotease (MMP)-9 [3] and osteopontin are increased in patients with synovitis compared to controls [4]. These studies indicate that biomarkers are a promising tool in detecting the destructive properties of joint damage.…”
Section: Pds-0104mentioning
confidence: 99%
“…To address these issues a meeting of experts in the field, including hematologists, orthopedic surgeons and physical therapists was held in Toronto, Canada in October 2014. The World Health Organization (WHO) International Classification of Function and Disability (ICF) model was used as a frame work to discuss the potential for developing a "core" set of outcome measures for use in persons with hemophilia treated with prophylaxis (3) ; a systematic review of selected outcome measures is in progress (4) . The results of this systematic review will identify areas that require further work including translation and culture adaptation of selected outcome measures for use globally.…”
Section: Pds-0104mentioning
confidence: 99%
See 1 more Smart Citation